Odpowiedzi

2010-03-04T16:48:15+01:00
A) -5x-x=-4-8
b) -2x-2x=7-7
c) -7x-11x=-5+41
d) 36x-14x= 14-36
e) 7x= 13+8
f) 3x-4x=4
g) 3x+3x=-9+9
Najlepsza Odpowiedź!
2010-03-04T16:54:17+01:00
A)-5x+4=x-8
6x=12/:6
x=2
b)-2x-7=2x-7
0=0
c)-7x+5=11x+41
-7x-11x=41-5
-18x=36/:(-18)
x=-2
d)36x-14=14x-36
36x-14x=-36+14
22x=-22/:22
x=-1
e)7x-13=8
7x=21/:7
x=3
f)3x-4=4x
3x-4x=4
-x=4/:(-1)
x=4
g)3x+9=-3x+9
3x+3x=9-9
6x=0
x=0
h)-27x-1=2x+59
-25x=60/:(-25)
x=2,4
i)45x-19=19x-45
45x+19x=-45+19
64x=-26/:64
x=-0,375
j)82x-9=-18x+1
82x+18x=10
100x=10/:100
x=0,1
2010-03-04T17:00:49+01:00
A)-5x+4=x-8 / +5x
4 = 6x - 8 / +8
12 = 6x
x = 12 : 6
x = 2

b)-2x-7=2x-7 / +2x
-7 = 4x - 7 / +7
0 = 4x / :4
x = 0

c)-7x+5=11x+41 / +7x
5 = 18x + 41 / -41
-36 = 18x / :18
x = -2

d)36x-14=14x-36 / +36
36x + 22 = 14x / -36x
22 = -22x / :(-22)
x = -1

e)7x-13=8 / +13
7x = 21 / :7
x = 3

f)3x-4=4x / -3x
-4 = x
x = -4

g)3x+9=-3x+9 / +3x
6x + 9 = 9 / -9
6x = 0 / :6
x = 0

h)-27x+1=2x+59 / -1
-27x = 2x + 58 / -2x
-29x = 58 / :(-29)
x = -2

i)45x-19=19x-45 / +45
45x + 26 = 19x / -45x
26 = -26x / :(-26)
x = -1

j)82x-9=-18x+1 / +9
82x = -18x + 10 / +18x
100x = 10 / :100
x = 0,1